A Tapestry of Human-Induced and Climate-Driven Environmental Change in Western Uganda: The Ndali Crater Lakes Region - Schmidt, Peter R.; Walz, Jonathan R.; Besigye, Jackline N.; Lejju, Julius B. (History in Africa, 2024)
Recent archaeological and paleo-environmental research in the Ndali Crater Lakes Region (NCLR) of western Uganda provide important new insights into anthropogenic impacts on moist forests to the East of the Rwenzori Mountains. This research significantly changes previous interpretations of paleo-environmental records in western Uganda and helps to distinguish climate change from human impacts. By drawing on multiple sources such as historical linguistics, archaeological evidence, and environmental proxies for change, a new picture emerges for a region that was a cultural crossroads for early Bantu-speakers and Central Sudanic-speakers between 400BCE and 1000CE. Detailed archaeological data and well-dated sites provide fine-grained evidence that closely fits episodes of significant environmental change, including a later and separate phase of forest clearance, soil degradation, and lake pollution caused by the saturation of the landscape by Bigo related populations between 1300 and 1650 CE.
Keywords: Uganda; Rwenzori Mountains; African Paleoenvironment; Kansyore; Bigo